Penal Mediation : Synchronization of Restorative Justice and Reflective Justice - Kurnianingsih, Marisa; Dewanto, Daffa Rafif; Mustofa, Yoesoef (Jurnal Mulawarman Law Review, 2024)
Restorative Justice is an alternative settlement of criminal cases involving the perpetrators, victims, family members and the victims as well as the authorities to settle disputes. Restorative justice began to develop in the 19th century and has been regulated in Indonesian legislation as in the Law No. In 2012, the Court of Appeal No. 15 of 2020, and the Police Regulations No. 8 in 2021. In its implementation it uses a criminal mediation mechanism involving law enforcement in the process of investigation, investigation and prosecution. There is no legal umbrella that specifically regulates Restorative Justice. In this study, the method of research used is the normative method of jurisprudence in which the study is carried out by the library. The aim of this research is to find out how the correspondence between the mechanisms and requirements in the settlement of criminal cases based on the rules in force in Indonesia on Restorative Justice. The method used is descriptive using secondary data is data obtained from library studies that are then analyzed with the rules, theories and opinions of relevant legal experts to obtain conclusions from the research. The results of this study of the setting on restorative justice still have differences between one and the other in the context of the type of behavior. In addition, restorative justice normatively has been in line with John Rawls’s concept of justice but in caseistic there are still some deviations from the rule.